RAS Mutation Clinical Risk Score to Predict Survival After Resection of Colorectal Liver Metastases. Issue 1 (January 2019) - Brudvik, Kristoffer W.; Jones, Robert P.; Giuliante, Felice; Shindoh, Junichi; Passot, Guillaume; Chung, Michael H.; Song, Juhee; Li, Liang; Dagenborg, Vegar J.; Fretland, Åsmund A.; Røsok, Bård; De Rose, Agostino M.; et al.
Abstract : Objective: To determine the impact of RAS mutation status on the traditional clinical score (t-CS) to predict survival after resection of colorectal liver metastases (CLM). Background: The t-CS relies on the following factors: primary tumor nodal status, disease-free interval, number and size of CLM, and carcinoembryonic antigen level. We hypothesized that the addition of RAS mutation status could create a modified clinical score (m-CS) that would outperform the t-CS. Methods: Patients who underwent resection of CLM from 2005 through 2013 and had RAS mutation status and t-CS factors available were included. Multivariate analysis was used to identify prognostic factors to include in the m-CS. Log-rank survival analyses were used to compare the t-CS and the m-CS. The m-CS was validated in an international multicenter cohort of 608 patients. Results: A total of 564 patients were eligible for analysis. RAS mutation was detected in 205 (36.3%) of patients. On multivariate analysis, RAS mutation was associated with poor overall survival, as were positive primary tumor lymph node status and diameter of the largest liver metastasis >50 mm. Each factor was assigned 1 point to produce a m-CS. The m-CS accurately stratified patients by overall and recurrence-free survival in both the initial patient series and validation cohort, whereas the t-CS did not. Conclusions: Modifying the t-CS by replacing disease-free interval, number of metastases, and CEA level with RAS mutation status produced an m-CS that outperformed the t-CS. The m-CS is therefore a simple validated tool that predicts survival after resection of CLM. Abstract : Supplemental Digital Content is available in the text